Caso Clínico ARP nº 23: Qual o seu diagnóstico? - Oliveira, Tiago (2022)
A 46-year-old female patient presented with a neck swelling with a progressive growth over the last 20 years. On physical examination, a pulsating firm painless mass was found on the right side of her neck, near the angle of the mandible. There were no pressure symptoms, and it was more mobile horizontally than vertically (Fontaine sign). Pulsations were felt on deep palpation and a faint bruit was heard on auscultation. Cervical computed tomography (CT) and digital subtraction angiography were performed for further investigation.